Dead in the water: a true story of hijacking, murder, and a global maritime conspiracy - Campbell, Matthew (Portfolio/Penguin, 2022)
"From award-winning journalists Matthew Campbell and Kit Chellel, the gripping, true-crime story of a notorious maritime hijacking at the heart of a massive conspiracy-and the unsolved murder that threatened to unravel it all. In July 2011, the oil tanker Brillante Virtuoso was drifting through the treacherous Gulf of Aden when a crew of pirates attacked and set her ablaze in a devastating explosion. But when David Mockett, a maritime surveyor working for Lloyd's of London, inspected the damaged vessel, he was left with more questions than answers. How had the pirates gotten aboard so easily? And if they wanted to steal the ship and bargain for its return, then why did they destroy it? The questions didn't add up-and Mockett would never answer them. Soon after his inspection, David Mockett was murdered. Dead in the Water is a shocking expose of the criminal inner workings of international shipping, told through the lens of the Brillante hijacking and its aftermath. Through first-hand accounts of those who lived it-from members of the ship's crew and witnesses to the attacks, to the ex-London detectives turned private investigators seeking to solve Mockett's murder and bring justice to his family-award-winning Bloomberg reporters Matthew Campbell and Kit Chellel piece together the astounding truth behind one of the most brazen financial frauds in history. The ambitious culmination of more than four years of reporting, Dead in the Water uncovers an intricate web of conspiracy amidst the lawless, old-world industry at the backbone of our new global economy"--